The Relationship Between Breastfeeding Pattern and the Risk of Postpartum Depression of Mothers in Tangerang - Angeline Tancherla; Melanie Widjaja (Medicinus, 2022)
Background and Aim: Postpartum depression (PPD) has a negative impact on mothers and children, such as breastfeeding (BF) disturbance. However, the relationship between BF pattern and PPD is still unclear due to contrasting results, and no related study has been done in Indonesia. Therefore this study is conducted to evaluate the relationship between BF pattern and the risk of PPD in mothers in Tangerang. Method: This is an analytic observational study with a cross-sectional design.  The samples of this study are 58 mothers that fulfill the inclusion criteria. Samples are chosen by the purposive sampling method. Data collection is conducted from January to April 2020. The results were analyzed using the SPSS program version 22.0 with the Chi-Square method. Results: There were 37 samples (63.8%) without PPD risk and 21 samples (36.8%) with PPD risk. Among 37 samples without PPD risk, 70.3% had exclusive BF and 29,7% had non-exclusive BF. Among 21 samples with PPD risk, 14.3% had exclusive BF and 85,7% had non-exclusive BF. The chi-Square analysis result showed that there is a significant association between BF pattern and PPD risk ( p=0.0001), with an OR of 0.071 (95% CI: 0.17-0.289).Conclusion: Breastfeeding pattern has a significant association with PPD risk. Exclusive BF has a protective effect on the risk of PPD at one month postpartum.